3D biomaterial matrix to support long term, full thickness, immuno-competent human skin equivalents with nervous system components. (April 2019) - Vidal, Sarah E. Lightfoot; Tamamoto, Kasey A.; Nguyen, Hanh; Abbott, Rosalyn D.; Cairns, Dana M.; Kaplan, David L.
Abstract: Current commercially available human skin equivalents (HSEs) are used for relatively short term studies (∼1 week) due in part to the time-dependent contraction of the collagen gel-based matrix and the limited cell types and skin tissue components utilized. In contrast, here we describe a new matrix consisting of a silk-collagen composite system that provides long term, stable cultivation with reduced contraction and degradation over time. This matrix supports full thickness skin equivalents which include nerves. The unique silk-collagen composite system preserves cell-binding domains of collagen while maintaining the stability and mechanics of the skin system for long-term culture with silk. The utility of this new composite protein-based biomaterial was demonstrated by bioengineering full thickness human skin systems using primary cells, including nerves and immune cells to establish an HSE with a neuro-immuno-cutaneous system. The HSEs with neurons and hypodermis, compared to in vitro skin-only HSEs controls, demonstrated higher secretion of pro-inflammatory cytokines. Proteomics analysis confirmed the presence of several proteins associated with inflammation across all sample groups, but HSEs with neurons had the highest amount of detected protein due to the complexity of the model. This improved, in vitro full thickness HSE model system utilizes cross-linked silk-collagen as the biomaterial and allows reduced reliance on animal models and provides a new in vitro tissue system for the assessment of chronic responses related to skin diseases and drug discovery.